Impact of Short and Moderate Rest Intervals on the Acute Immunometabolic Response to Exhaustive Strength Exercise: Part i - Rossi, Fabrício E. [UNESP]; Gerosa-Neto, Jose [UNESP]; Zanchi, Nelo E.; Cholewa, Jason M.; Lira, Fabio S. [UNESP] (Wolters Kluwer, 2016)
Rossi, FE, Gerosa-Neto, J, Zanchi, NE, Cholewa, JM, and Lira, FS. Impact of short and moderate rest intervals on the acute immunometabolic response to exhaustive strength exercise. J Strength Cond Res 30(6): 1563-1569, 2016 - The purpose of this study was to verify the influence of the short and moderate intervals of recovery in response to an acute bout of exhaustive strength exercise on performance, inflammatory, and metabolic responses in healthy adults. Eight healthy subjects (age 24.6 ± 4.1 years) performed 2 randomized sequences: short 70% of 1 repetition maximum (1RM) with 30 seconds of rest between sets; moderate 70% of 1RM with 90 seconds of rest between sets. All sequences of exercises were performed over 4 sets until movement failure in the squat and bench press exercises, respectively. The total number of repetitions performed was recorded for each set of each exercise for all sequences. The percentages of fat mass and fat-free mass were estimated by dual-energy x-ray absorptiometry. Glucose, tumor necrosis factor-α, interleukin (IL)-6, IL-10, and nonester fatty acid were assessed, at baseline, immediately after exercise, after 15 and 30 minutes. When compared with the maximum number of repetitions and the total weight lifted, there was a statistically significant decrease after both intervals. The only statistically significant decreases over time occurred at the post-15 minutes assessment of the IL-6 and glucose when a moderate interval of recovery was performed. When comparing the alterations between the pools (the mean of the cluster of all periods in each variable), there was a statistically significant increase on the IL-6 and IL-10 when a moderate interval of recovery was performed again, however, not considering a statistical difference on the IL-10. Thus, we concluded that different interval of recovery in response to exhaustive strength exercise decreases performance but in only moderate intervals, it is associated with inflammatory and metabolic response.
Keywords: inflammation; interval of recovery; metabolism